Facing death, returning to life: A qualitative analysis of MDMA-assisted therapy for anxiety associated with life-threatening illness - Barone, William; Mitsunaga-Whitten, Michiko; Blaustein, Lia Osunfunláyò; Perl, Phillip; Swank, Marisa; Swift, Thomas Cody (Frontiers in Psychiatry, 2022)
Anxiety associated with life-threatening illness (LTI) is a pervasive mental health issue with a wide impact. A spectrum of traditional pharmacotherapies and psychotherapies are available, but offer varying success in reducing symptoms and improving quality of life. We explore a novel therapy for this condition by assessing prominent thematic elements from participant narrative accounts of a pilot phase 2 clinical trial of 3,4 Methylenedioxymethamphetamine-Assisted Therapy (MDMA-AT) for treating anxiety associated with LTI. Semi-structured qualitative interviews were conducted with a subset of adult participants 3 months following completion of this trial. This qualitative analysis sought to complement, clarify, and expand upon the quantitative findings obtained from the clinical trial to further understand the process and outcomes of the treatment. Interviews were coded and analyzed using an Interpretative Phenomenological Analysis (IPA) methodological framework. Participants described in detail their experiences from before, during and after the trial, which were analyzed and categorized into thematic clusters. Specifically, participants explored what they felt were important elements of the therapeutic process including processing trauma and grief, exploring mystical and existential experiences, engaging with the present moment with reduced physiological activation, and facing illness and existential fears. Outcomes of the treatment included increased ability to cope with LTI, reduced psychological symptoms, improved vitality and quality of life, and feeling more resourced. Participant narratives also showed a reconnection to life and greater emotional resilience in response to trauma and medical relapse. These findings are compared to similar treatments for the same indication. Limitations and challenges encountered in conducting this study are discussed along with implications for theory and clinical treatment.